20.6k views
0 votes
Mrs. Goldberg wrote the expression on the board.

Where could she place brackets in the expression for it to be equal to 63?

A.
[3 + 2 × 23] − 4 + 11
B.
3 + 2 × [23 − 4 + 11]
C.
[3 + 2] × 23 − 4 + 11
D.
3 + 2 × 23 − [4 + 11]

User Kuhlemann
by
5.4k points

1 Answer

3 votes

Answer:

for the first one: i don't know...i think it can't be done.for the second one, it is : 4 × (2 + 3) - 1 = 19for the third one, it is 4 + ((3² +1) ÷ 5) = 6for the fourth one, it is : (3 + 2) × 6 - 3 = 27for the fifth one, it is : 7 + 4 - (9 ÷ 3) = 8for the sixth one, it is : (6 ÷ 2) + (4 × 2) = 11for the seventh one, it is : (3 + 1)² ÷ 4 = 4for the eight one, it is : (12 + 20) ÷ 4² = 2for the ninth one, it is : 7 + (7 - 18 ÷ 6)² = 23

Explanation:

hope this helps

User Hyzyr
by
6.0k points